2013
DOI: 10.1038/nrn3444
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the classification and nomenclature of cortical GABAergic interneurons

Abstract: A systematic classification and accepted nomenclature of neuron types is much needed but is currently lacking. This article describes a possible taxonomical solution for classifying GABAergic interneurons of the cerebral cortex based on a novel, web-based interactive system that allows experts to classify neurons with pre-determined criteria. Using Bayesian analysis and clustering algorithms on the resulting data, we investigated the suitability of several anatomical terms and neuron names for cortical GABAerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
722
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 748 publications
(744 citation statements)
references
References 30 publications
19
722
1
2
Order By: Relevance
“…We argue that STSP may have evolved of necessity to enable more complex computations in local circuits. The existence of STSP is furthermore expected, since the nodes of biological neuronal networks are made up of dozens of different cell types [70][71][72]. Presumably, these different cell types need to be governed by distinct synaptic plasticity learning rules, because activity patterns and excitabilities vary tremendously with cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that STSP may have evolved of necessity to enable more complex computations in local circuits. The existence of STSP is furthermore expected, since the nodes of biological neuronal networks are made up of dozens of different cell types [70][71][72]. Presumably, these different cell types need to be governed by distinct synaptic plasticity learning rules, because activity patterns and excitabilities vary tremendously with cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Although a natural next step in computer modeling might seem to require incorporating considerably more detail, our review highlights just how much detail there is. For every cell type -and there is a lot of them [70][71][72] -there is a corresponding multiplicity of STSP learning rules and short-term dynamics. Yet, to understand the brain and synaptic diseases such as autism, anxiety, or epilepsy [81], it appears that we have no choice but to grapple with STSP.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the GABA system is incredibly diverse, making it difficult to determine what are the effects of specific GABAergic system deficits at the level of synaptic circuitry (Ascoli et al, 2008;DeFelipe et al, 2013). It appears that schizophrenia is characterized by dysfunction of multiple interneuronal cell types (Lewis et al, 2005).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Mature interneurons can be distinguished by their molecular content, electrical properties, synaptic targets and laminar distributions (Ascoli et al, 2008;DeFelipe et al, 2013;Markram et al, 2004). Interneuron cell types typically contain either the calcium binding proteins, such as parvalbumin (PV), calretinin (CR), or calbindin (CB), or the neuropeptides, such as cholecystokinin (CCK), neuropeptide Y (NPY), somatostatin (SST), or vasointestinal peptide (VIP), but occasionally contain more than one of these markers (Ascoli et al, 2008;Markram et al, 2004).…”
Section: Development Of the Gabaergic Systemmentioning
confidence: 99%
“…In cortex, though the discussion has not been fully settled, it has been difficult to agree on a definite classification of cortical interneurons as has been attempted. 12 In general, intermediary cell types are observed that seem to defy the classification scheme, whether one uses schemes based on morphology, physiology and molecular markers 13 or on gene expression. 14 Conversely, a recent bigdata study 15 reports that it is sufficient to use 3 simple connectivity motives to come to a definite classification, suggesting that also in cortex it may be more useful to consider broader groupings of cell types instead of clearly separable types.…”
mentioning
confidence: 99%